The Impact of Uzbek-language Mobile Libraries on Digital Education - Mannonov, Abdurahim; Rahmonov, Husanboy; Kodirova, Kamala; Jalolova, Shakhnoza; Bayeshanov, Abdulla; Khamidova, Sevara; Atajanov, Sarvar; Karimov, Umrbek (Indian Journal of Information Sources and Services, 2025)
This paper discusses the potential to transform digital education in Uzbekistan, especially in underserved and rural areas, through the use of Uzbek-language mobile libraries. Internet penetration being relatively low and digital content in the Uzbek language limited, mobile libraries offer a localized, low-cost, and culturally appropriate answer to closing the digital education gap. Based on international models and exemplary implementations in Samarkand and Bostanlyk regions, the research emphasizes how mobile libraries contribute to digital inclusion, increase literacy rates, and facilitate lifelong learning. The article also discusses key challenges like technological restraints, limited budgets, and low digital literacy, and outlines innovative approaches towards ensuring sustainability, scalability, and impact. Finally, Uzbek-language mobile libraries are set to be important tools in democratizing access to information, empowering communities, and enhancing Uzbekistan's digital education infrastructure. Keywords: Uzbek-language Mobile Libraries, Digital Education, Rural Education, Digital Inclusion, Literacy Development, Educational Technology, Mobile Librarianship, Community Empowerment, Educational Equity, Uzbekistan